2018
DOI: 10.15208/beh.2018.22
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and client satisfaction of Islamic and conventional banks: A bilateral effect

Abstract: In this paper, we investigate the possible bidirectional causal relationship between bank efficiency and client satisfaction in the banking sector of Kuwait. For this purpose, we applied structural equation model (SEM) methodology. Based on a 5-point Likert scale questionnaire, data was gathered from Islamic banks (IBs) clients and conventional banks (CBs) client. We found a significant evidence of a, relatively, higher client satisfaction for IBs. The findings, also, provide evidence of a positive and signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…They found no differences in satisfaction levels between the two groups concluding that Islamic banks needed to be competitive, improve their service delivery and provide transparent information regarding their business operations. In stark contrast, Aldeehani (2018) found that in Kuwait, customers of the Islamic bank are more satisfied than customers of conventional banks. Furthermore, they found a significant positive bilateral causal relationship between client satisfaction and banking efficiency.…”
Section: Customer Satisfactionmentioning
confidence: 82%
See 1 more Smart Citation
“…They found no differences in satisfaction levels between the two groups concluding that Islamic banks needed to be competitive, improve their service delivery and provide transparent information regarding their business operations. In stark contrast, Aldeehani (2018) found that in Kuwait, customers of the Islamic bank are more satisfied than customers of conventional banks. Furthermore, they found a significant positive bilateral causal relationship between client satisfaction and banking efficiency.…”
Section: Customer Satisfactionmentioning
confidence: 82%
“…This finding indicates that if the objectives of an Islamic bank align with the requirements of the Sharia, it increases the chances of Muslim customers being satisfied. This finding adds one more dimension to the factors contributing to customer satisfaction, which includes, among other things, the products and services offered, efficiency and image of the Islamic bank (Aldeehani, 2018;Amin et al, 2013;Khan et al, 2007). A positive and significant relationship (b = 0.21; P < 0.01) was also found between the objectives of Islamic banking and customer loyalty.…”
Section: Jimamentioning
confidence: 95%
“…Such a contradicting finding appeals future theoretical and empirical studies to shed more light on the issue of interactions between IBs and CBs in a dual banking system context. The recent study of Samad (2018) claiming the existence of a causal relationship between IBs’ return on deposits and CBs’ creditor interest rate, and the one of Aldeehani (2018) showing how client satisfaction is a determinant factor for bank efficiency for both IBs and CBs, provide further evidence on the existence of such interactions.…”
Section: Econometric Analysismentioning
confidence: 85%
“…It also appeals future research studies to consider the issue of policies to adopt by IBs to further increase their “PLS” funding. The studies by Zarrouk et al (2016), Javaid and Alalawi (2018), Kamarudin et al (2018), Cham (2018) and Aldeehani (2018) reviewed above can help in bringing some elements of answer to this specific issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation